Innovative Treatments for Mucopolysaccharidoses - Lagler, Florian B. (Journal of Child Science, 2018)
Mucopolysaccharidoses (MPSs) are caused by deficiency of specific lysosomal enzymes that affect the degradation of mucopolysaccharides or glycosaminoglycans. Since more than 15 years enzyme replacement therapies are available for an increasing number of MPSs. These therapies together with hematopoietic stem cell transplantation today are the gold standard of causal treatment in MPS. Despite confirmed efficacy, both do not cure these severe conditions. In this article, we discuss the limitations of established and promises of emerging therapies. The limitations of intravenous enzyme replacement and cell therapy can be summarized as immune reactions against the therapeutic molecules/cells and the failure to restore enduring and sufficient enzyme concentration in all relevant tissues. Accordingly, innovative approaches comprise small molecules and encapsulated cells that do not activate antitherapeutic immune reactions, several gene therapy approaches that aim for sustained enzyme expression, and new enzymes that penetrate blood–brain and other barriers for drug distribution. This article provides an update on the state of development of these new therapies and highlights enduring challenges.
Keywords: mucopolysaccharidoses; gene therapy; innovative therapies; cell therapy; pharmacology